Hyleina kaphetea, a new genus and species of clearwing moths from tropical Africa (Lepidoptera: Sesiidae: Sesiini) - Bartsch, Daniel (Zootaxa, 2017)
A new species and genus of Sesiini, Hyleina kaphetea new gen. & new sp., from tropical Africa is described. The type series comprises twelve male specimens from the Democratic Republic of Congo, Malawi, Tanzania and Zambia. Female specimens and life history are unknown.